Machine Learning and Mechanics Based Soft Computing Applications - Nguyen, Thi Dieu Linh.; Lu, Joan. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book highlights recent advances in the area of machine learning and robotics-based soft computing applications. The book covers various artificial intelligence, machine learning, and mechanics, a mix of mechanical computational engineering work. The current computing era has a huge market/potential for machine learning, robotics, and soft computing techniques and their applications. With this in view, the book shares latest research and cutting-edge applications useful for professionals and researchers in these areas.
Chapter 1 - LS-TFP: A LSTM-Based Traffic Flow Prediction Method in Intelligent Internet of Things -- Chapter 2 - Threshold Text Classification with Kullback-Leibler Divergence Approach -- Chapter 3 - Cellular Automata-based Simulation Model for Water Quality Management of Pangasius Ponds -- Chapter 4 - Deep-IDS: A lightweight Neural Network based Intrusion Detection System -- Chapter 5 - Heuristic methods solving Markowitz Mean-Variance portfolio optimization problem -- Chapter 6 - Context-based and Collaboration-based Product Recommendation Approaches for a Clothes Online Sale System -- Chapter 7 - Recommendation Approaches for a Clothes Online Sale System -- Chapter 8 - A cost-effective control system of the biogas based electrical generator -- Chapter 9 - Parallel, Distributed Model-checking of Composite Web-services with Integrated Choreography and Orchestration -- Chapter 10 - An application of logistic regression model in the student's academic performance at HUST, Vietnam -- Chapter 11 -Soft Robotics Fingered-Hand Based on Working Principle of Asymmetric Soft Actuator -- Chapter 12 - Control design for 400Hz Ground Power Unit -- Chapter 13 - Rapid design of square-spiral metamaterial for Enhanced Wireless power transfer applications using Artificial Neural Networks -- Chapter 14 - GIS and RS application for Land use status quo mapping in 2020 and Land use change assessing in Thu Dau Mot city -- Chapter 15 - Particle Swarm Optimization for Acceleration Tracking Control of an Actuator System -- Chapter 16 - Count the Number of Steel Bars based on Deep Learning -- Chapter 17 - Hybrid SARIMA - GRU model based on STL for forecasting water level in Red river North Vietnam -- Chapter 18 - Activity Based Learning: An Analysis to Teach Learners Using Online Methodologies -- Chapter 19 - Use of a Fatigue Framework to Adopt a New Normalization Strategy for Deep Learning Based Augmentation -- Chapter 20 - An Innovative and Smart Agriculture Platform for Improving the Coffee Value Chain and Supply Chain -- Chapter 21 - Complex Shear Imaging Based on Signal Processing and Machine Learning Algorithms -- Chapter 22 - Breast Cancer Detection Based on UWB Dataset And Machine Learning -- Chapter 23 - A review of mathematical methods for flexible robot dynamics modeling and simulation -- Chapter 24 - Digital Twins of Robotic Systems: Increasing capability for industrial applications -- Chapter 25 - Optimal Motion for Humanoid Robotic Arms using Kinect Camera -- Chapter 26 - 6G Wireless Communication Systems and Its Applications -- Chapter 27 - Compensation Techniques for Non-linear effects using NG-RoF-DSP: A Review -- Chapter 28 - An IoT solution designed for remote automatic control and supervisor systems to key environmental factors and diseases in coffee farms in Vietnam -- Chapter 29 - Artificial Intelligence As a Strategic partner to HRM 4.0.
Keywords: Computational intelligence; Artificial intelligence; Robotics; Machine learning; Computational Intelligence; Artificial Intelligence; Robotics; Machine Learning